A rodent model for Wilms tumors: embryonal kidney neoplasms induced by N-nitroso-N'-methylurea. - Sharma, P M (1994)
Embryonal kidney cell tumors develop in rats given the alkylating agent N-nitroso-N'-methylurea as neonates. These tumors resemble the childhood Wilms tumors in their histopathology. Deletions and mutations in the Wilms tumor suppressor gene, WT1, are present in up to 6% of childhood nephroblastomas. To investigate the role of WT1 in rat kidney tumorigenesis, we studied the genetic alterations in WT1 and its target genes. Point mutations were found in WT1 cDNA in 7 of 18 kidney tumors. Mesenchymal tumors contained G-->A transition mutations in codons 128, 364, and 372, typical of the methylating action of N-nitroso-N'-methylurea on DNA. Each of the four nephroblastomas contained the same T-->A mutation at codon 111 of WT1, reflective of transversion mutagenesis by N-nitroso-N'-methylurea in vivo. Like Wilms tumors, mRNA levels of WT1, IGF2, Pax-2, and MK genes were higher than newborn kidney in the majority of the tumors. The histopathology of the rat kidney tumors and the genetic alterations are reminiscent of those observed in Wilms tumors, establishing this as a relevant model system for the human disease.